In vitro toxicological evaluation of pouched portioned oral nicotine products - Keyser, Brian M.; Leverette, Robert; McRae, Reagan; Wertman, John; Shutsky, Tom; Szeliga, Ken; Makena, Patrudu; Jordan, Kristen G. (Frontiers in Toxicology, 2024)
IntroductionModern oral nicotine pouch products (ONPs) are a category of oral nicotine products which contain pharmaceutical-grade nicotine, flavors, and other food-grade ingredients but no tobacco leaf. Recent reports indicate that ONPs in general do not contain (or only at minimal levels) the harmful and potentially harmful constituents (HPHCs) identified in cigarette smoke, suggesting their potential as alternative products for reducing harm from cigarette smoking.MethodsWe assessed in vitro toxicological effects of eight ONPs, designated as modern oral (MO) 1 to 8 along with an ONP, an oral tobacco (snus), and a combustible cigarette market comparator using established regulatory toxicological assays including Ames, in vitro micronucleus (ivMN), and neutral red uptake (NRU) assays.ResultsThe MO test products 1-7 ZYN wintergreen, and General Snus white mint were negative for mutagenicity (Ames assay), genotoxicity (ivMN), and cytotoxicity (NRU). The combustible cigarette was positive in all three assays. The MO-8 test product was negative for mutagenicity; however, it was positive in the ivMN and NRU assays at concentrations either 42 to 135-fold based on the ivMN i to iv treatment schedule or 60-fold higher, respectively, when compared to combustible cigarettes.DiscussionThus, the MO test products are likely to be less harmful than combustible cigarettes and are alternatives to cigarettes. However, understanding of long-term effects of ONPs in general requires additional research.